Determinants of Entrepreneurial Intention - Prabawati, Arrum; Rusdarti, Rusdarti; Santoso, Jarot Tri Bowo (Universitas Negeri Semarang, 2024)
Entrepreneurial intention is a person's determination to become an entrepreneur or to engage in entrepreneurial activities. According to survey data regarding the number of students engaged in entrepreneurship at the Faculty of Economics and Business at Universitas Negeri Semarang, it is evident that students' awareness of entrepreneurship is still low. Therefore, there is a need to enhance students' entrepreneurial intentions. This study aims to examine the influence of entrepreneurial knowledge, entrepreneurial motivation, and digital literacy on entrepreneurial intention through self-efficacy. The population in this study consists of 1,227 students from the Faculty of Economics and Business, class of 2020, at Universitas Negeri Semarang. The sample size was determined using Slovin's formula, resulting in 155 respondents. The sampling technique employed was proportionate random sampling. Data collection was conducted using a questionnaire that had been tested for validity and reliability. The data analysis techniques included descriptive analysis, path analysis, and the sobel test. The results of the study indicate that (1) entrepreneurial knowledge, entrepreneurial motivation, and digital literacy influence self-efficacy; (2) entrepreneurial knowledge, entrepreneurial motivation, and digital literacy influence entrepreneurial intention through self-efficacy; (3) self-efficacy influences entrepreneurial intention. This study is expected to contribute to the development of scientific knowledge and to test the theory of planned behavior related to entrepreneurial intention as a basis for enhancing students' entrepreneurial intentions.